Impact of Academic Library Resources on Learning and Research among Nursing and Midwifery Students at the University Of Jos - Shittu Lukman Olayinka; Favour Ehi Attah; Ardi Alfaris (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2024)
This study investigated impact of academic library resources on learning and research among nursing and midwifery students at the University of Jos. the study was guided by four objectives and the study also answered four research questions. The population comprised 515 undergraduate students from the Department of Nursing and Midwifery, University of Jos, during the 2020/2021 academic session, encompassing students from 100 to 500 levels. A sample of 200 students was selected using proportional stratified sampling, ensuring representation from all levels and both genders. The sampling fraction of 0.24% was applied to each stratum to determine the sample size for each level. Data collection was facilitated through a researcher-developed structured questionnaire titled “Students’ Questionnaire on Influence of Academic Library on Learning and Research among Nursing and Midwifery Students” (SQIALLRNMS). The questionnaire underwent expert validation to ensure relevance, accuracy, and adequacy. Reliability was established using the internal consistency form of reliability through split-half method, yielding a coefficient of 0.76. Data analysis was conducted using descriptive and inferential statistics via SPSS software. The study revealed among other things that, academic library has significant positive influence on learning of undergraduate nursing and midwifery students in the university of Jos. Also that, academic library significantly influences research writing and development among undergraduate nursing and midwifery students in the university of Jos among others. The study also recommended among other things that, students should be sensitized on the need to use library services and how to judiciously utilize the library to improve their learning and research and that, there should be training and retraining of library staff for their attitude and ways of assisting users to better use the library services among others.